ASSESSMENT OF CHANGES IN THE TURNOVER OF LITHUANIAN RETAIL TRADE ENTERPRISES IN 2001–2008 - Vengrauskas, Petras Vytautas; Mackevičius, Vytautas (Ekonomika, 2010)
The paper presents an analysis of the methodological side of assessing the turnover of Lithuanian retail trade enterprises, i.e. the indicators to be employed in assessing changes in the volume and composition of the turnover over a longer term, their relationship with other national economic indicators, as well as their theoretical and practical significance. The analysis of changes in the volume and composition of the turnover of Lithuanian retail enterprises in 2000–2008 has revealed its positive and negative trends and the factors influencing these changes. The period under consideration is remarkable in that the years 2000–2001 marked the recovery of the Lithuanian economy after the financial crisis in Russia, its growth until the third quarter of 2008 and the beginning of its decline. The paper summarizes trends in and problems of changes in the volume and composition of the turnover of the country’s retail trade enterprises in the period under consideration and shows the possibilities for its development.